2018
DOI: 10.1038/s41598-018-32467-2
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic introgression: evidence that selection and plasticity mask the full phenotypic potential of domesticated Atlantic salmon in the wild

Abstract: Domesticated Atlantic salmon grow much faster than wild salmon when reared together in fish tanks under farming conditions (size ratios typically 1:2–3). In contrast, domesticated salmon only display marginally higher growth than wild salmon when reared together in rivers (size ratios typically 1:1–1.2). This begs the question why? Is this a difference in the plastic response driven by divergent energy budgets between the two environments, or is it a result of selection, whereby domesticated salmon that displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 68 publications
(103 reference statements)
10
39
0
Order By: Relevance
“…conclusion Fish domestication, despite being investigated for decades, still raises many questions, but the present study clearly shows that the effect of the domestication process in Eurasian perch can be observed from the very first days of larvae life. It can be suggested that the differences observed in the present study are stemming from either phenotypic plasticity 75 , epigenetic pattern 76 or maternally derived modification of the transcriptomic 'cargo' determining embryonic and larval performance in finfishes 20 . Besides, the simulataneous involvement of all the three proceses in conditioning the differences between the wild and domesticated stocks can not be excluded.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…conclusion Fish domestication, despite being investigated for decades, still raises many questions, but the present study clearly shows that the effect of the domestication process in Eurasian perch can be observed from the very first days of larvae life. It can be suggested that the differences observed in the present study are stemming from either phenotypic plasticity 75 , epigenetic pattern 76 or maternally derived modification of the transcriptomic 'cargo' determining embryonic and larval performance in finfishes 20 . Besides, the simulataneous involvement of all the three proceses in conditioning the differences between the wild and domesticated stocks can not be excluded.…”
Section: Discussionmentioning
confidence: 79%
“…Stress affects the functioning of the entire organism, as well as the digestive tract, and it could cause, for example, changes in stomach and intestinal secretion and changes in absorption capacity in the intestine 73,74 . Stress can also negatively affect the modification of the intestinal microflora, which -if functioning properly -supports digestion, metabolism and provides significant protection against pathogens 74,75 . It was shown that in Eurasian perch exposed to stress caused by the presence of predators and food shortages that the number of 'favourable' intestinal microflora decreased significantly, which affects overall fish welfare 74 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, farmed or growth hormone implanted salmon rapidly outgrow salmon of the wild type in captivity with high and reliable access to food (Solberg, Zwei, Nilsen, & Glover, 2013b;Sundt-Hansen et al, 2012). This trend is much less prominent and may even be reversed under natural conditions where food access is typically less reliable and scarce (Glover, Solberg, Besnier, & Skaala, 2018;Reed et al, 2015;Sundt-Hansen et al, 2012). Hence, we hypothesize that the performance of farmed salmon offspring, as well as their ability to outcompete wild salmon, depends on food availability.…”
Section: Introductionmentioning
confidence: 96%
“…Over the past decade, we have studied an experimental population of domesticated and wild Atlantic salmon and their crosses at the aquaculture facility owned by the Institute of Marine Research located in Matre, western Norway (Solberg et al 2013;Solberg et al 2014;Ayllon et al 2015;Harvey et al 2016;Glover et al 2018;Harvey et al 2018). The reader is directed to these publications for full details regarding the standard rearing conditions experienced in this fish farm.…”
Section: Experimental Crossesmentioning
confidence: 99%
“…Total DNA from all offspring and parents was purified using the Qiagen DNeasy Blood & Tissue Kit (Qiagen, Hilden, Germany) according to the manufacturer´s recommendations Microsatellite DNA parentage testing was used to unambiguously identify the pedigree of all individuals used in this study using the exclusion based method implemented in FAP (Taggart 2007). The laboratory conducting these analyses has extensive experience in DNA parentage testing (Solberg et al 2013;Solberg et al 2014;Harvey et al 2016;Glover et al 2018;Harvey et al 2018), and the full details regarding the markers used and their amplification conditions are available in these previous studies. In addition to microsatellites, a set of 116 genome-wide distributed SNPs were genotyped in all offspring and parents for the purpose of linkage mapping (see below).…”
Section: Genetic Analysis -Microsatellites and Snpsmentioning
confidence: 99%